KARAKTER MORFOLOGI HIBRID ACACIA (A. mangium x A. auriculiformis) DI PERSEMAIAN - Sri Sunarti (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
The superiority of Acacia hybrid (A. mangium x A. auriculiformis) compared to the parent trees as fast growth, straight bole, ligth branching, more tolerance to pest and desease and had better wood properties. In order to maintain the superiority, it should be propagated vegetatively. However, the propagation potential of Acacia spp usually decreased by increasing the age of plant (aging effect). To prevent the aging effect on Acacia hybrid, vegetative propagation of selected trees should be done before becoming too old. This study was aimed to observe morphological seedling characteristics of Acacia hybrid. The result showed that morphological seedling characteristics of Acacia hybrid were intermediate between the parents species. The development of leaves pattern was well-marked by absence of 4-pinnates leaves or number of pinnates leaves was between 4-6. In addition, the pubescence was present on the margin of pinnates and the number of main vein on phyllode were mostly 3.